PEMBUATAN BUBUK CABE MERAH MENGGUNAKAN VARIASI JENIS CABE DAN METODE PENGERINGAN - HP, Sudaryati; MS, Latifah; Hermawan, Donny Eko (UPN VETERAN JAWA TIMUR, 2011)
Chili powder is a product in the form of powder, practically in the preparation and have a long shelf life. This is the nature of the powder product having a very small particle size, has a low water content. Chili powder manufacturing process were sorting, washing and cleaning the stem, drying, milling and sieving. This study aims to find the best results from different type of chili with different dryers include: Oven, Freeze Dryer and Cabinet dryer on the quality of red chili powder. Tthe results obtained from the data the best treatment of red chili powder using a freeze dryer as follows: The water content of 15.8679%, β-carotene 318.728 IU, vitamin C 563.017 (mg/100g), color (L * 42.40; 20.25 b * 18.60) and organoleptic tests of color (83.5).Keywords : chili powder, cabinet drier, oven, freeze drier